Ozone Remote Measurement in Tuxtla Gutiérrez, Chiapas, Mexico, Using the DOAS Technique - García-Lara, C.; Nájera Aguilar, H.; Camas-Anzueto, J.; Mendoza-Vazquez, S. (Revista Cubana de Física; Vol 30 No 2 (2013), 2013)
A brief description of a remote pollutants monitoring system based on passive differential optical absorption spectro-scopy, which detects atmospheric trace gases is presented. This system was placed in the UNICACH campus facilities for monitoring a linear extension approximately 2.9 km. It was determined the concentration of ozone in the area of interest, also evaluating the influence of climatic conditions in the obtained results which finally were compared with a detection system used by the government dependence SEMAVIH, observing a good correlation between them.